Authentication Model Using Multiple Sensors Input - Bani Hashim, Ahmad Yusairi; Nawawi, Badrul Hisyam; Shafii, Mohd Hanafi; Abdul Rahim, Mohd Riyadh Solihin (2009)
This paper presents a non-novel way of mathematical abstraction, but unique in design approach to a security system. It offers solution to an authentication model for an access control system that has multiple inputs. The approach discussed comprise of procedures that begins by assigning definitions to every components, the flow of information, and ends through execution styles. It has been tested roughly using some off-the-shelf software and equipment. The results show that fusion of data obtained from various sensors is possible by following a prescribed architecture that intrusion activity performed by unwanted persons should be difficult.